Thermal Modeling of the Injection of Standard and Thermally Insulated Cored Wire - Castro-Cedeno, E.-I.; Jardy, A.; Carré, A.; Gerardin, S.; Bellot, J. P. (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2017)
Cored wire injection is a widespread method used to perform alloying additions during ferrous and non-ferrous liquid metal treatment. The wire consists of a metal casing that is tightly wrapped around a core of material; the casing delays the release of the material as the wire is immersed into the melt. This method of addition presents advantages such as higher repeatability and yield of cored material with respect to bulk additions. Experimental and numerical work has been performed by several authors on the subject of alloy additions, spherical and cylindrical geometries being mainly considered. Surprisingly this has not been the case for cored wire, where the reported experimental or numerical studies are scarce. This work presents a 1-D finite volume numerical model aimed for the simulation of the thermal phenomena which occurs when the wire is injected into a liquid metal bath. It is currently being used as a design tool for the conception of new types of cored wire. A parametric study on the effect of injection velocity and steel casing thickness for an Al cored wire immersed into a steel melt at 1863 K (1590 °C) is presented. The standard single casing wire is further compared against a wire with multiple casings. Numerical results show that over a certain range of injection velocities, the core contents’ release is delayed in the multiple casing when compared to a single casing wire.